Denervated muscle extract promotes recovery of muscle atrophy through activation of satellite cells. An experimental study - Eduardo Agüera; Salvador Castilla; Evelio Luque; Ignacio Jimena; Ignacio Ruz-Caracuel; Fernando Leiva-Cepas; José Peña (Journal of Sport and Health Science, 2019)
Purpose: The objective of the present study was to determine whether a denervated muscle extract (DmEx) could stimulate satellite cell response in denervated muscle. Methods: Wistar rats were divided into 4 groups: normal rats, normal rats treated with DmEx, denervated rats, and denervated rats treated with DmEx. The soleus muscles were examined using immunohistochemical techniques for proliferating cell nuclear antigen, desmin, and myogenic differentiation antigen (MyoD), and electron microscopy was used for analysis of the satellite cells. Results: The results indicate that while denervation causes activation of satellite cells, DmEx also induces myogenic differentiation of cells localized in the interstitial space and the formation of new muscle fibers. Although DmEx had a similar effect in nature on innervated and denervated muscles, this response was of greater magnitude in denervated vs. intact muscles. Conclusion: Our study shows that treatment of denervated rats with DmEx potentiates the myogenic response in atrophic denervated muscles. Keywords: Muscle atrophy, Muscle denervation, Muscle extract, Myogenic response, Satellite cell, Skeletal muscle